DEVELOPMENT OF LEARNING INSTRUMENTSPROBLEM BASEDTO IMPROVE PHYSICSLEARNING OUTCOMES ON TOPICS STATIC FLUID - Pretti TM Ambarita (Jurnal Pendidikan Fisika, 2017)
The objective of this research were to produce a lesson plans and worksheets learning instrument design that corresponded to problem based learning models and analyze whether it was can improve student learning outcomes. This research development was done inclassroom by using development research methods of AnalysisDesign Development Implementation and Evaluation (ADDIE). ADDIE method was used as a method for designing a lesson plans and worksheets that corresponded to it. Three stages of development of lesson plans and worksheets such as an assessment by a team of experts, small group, and a field test.Assessment by a team of experts based on theree aspects such as format, content, and language. In small group and field test based on a response of studentssheet. The student response sheetcontains of teacher's ability to teach. Worksheet assessment based on aspects of the format, content, and language. Assessment of student learning outcomes based on pretest and posttest were analyzed by n-gain. The results of development of lesson plans and worksheets were validated by a team of experts on aspects of format, content, and language. The result both of development of lesson plans and worksheets in small group and field test produced good categories. There was an increased student learning outcomes of first to third meeting with categories of low to moderate